Pedagogik Futuristik: Paradigma Baru Pendidikan dalam Membangun Generasi Emas Indonesia 2045 - Agam Aris Munandar; Yusuf Tri Herlambang; Tatang Muhtar (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
Education is a key factor in shaping the future of a nation, particularly in realizing Indonesia's Golden Generation 2045, which is excellent and globally competitive. Conventional educational paradigms are considered insufficient to accommodate the increasingly complex demands of the times, necessitating a more adaptive and innovative approach. This study aims to analyze the urgency of implementing Futuristic Pedagogy as an educational paradigm that equips students with 21st-century skills, such as critical thinking, creativity, collaboration, and digital literacy. This research employs a literature review method by analyzing various sources related to the concept of Futuristic Pedagogy and its implementation in the education system. The findings indicate that Futuristic Pedagogy emphasizes technology integration, project-based learning, as well as a more collaborative and inclusive approach to enhance the relevance of education in meeting future needs. The successful implementation of this paradigm requires support from various stakeholders, including the government, educators, and society.Thus, Futuristic Pedagogy is not merely a theoretical concept but an urgent necessity in building an innovative, adaptive generation ready to face global challenges, ultimately contributing to the realization of Indonesia's Golden Generation 2045.